Making history in 1 h: how sex, aging, technology, and elevation affect the cycling hour record - Harnish, C. R.; Swinand, G. P.; Fisher, A. E. (Medicine & Science in Sports & Exercise, 2024)
Purpose The purpose of this article was to analyze more than a century of cycling hour records (CHR) to examine the effects of sex, age, and altitude on cycling performance. Our hypotheses were that men`s performance (distance) would exceed those of women by more than 10% but would decline at similar rates with aging and that altitude would have a small benefit, which might reach a maximum.